2001
DOI: 10.1111/j.1096-0031.2001.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Majority Does Not Rule: The Trouble with Majority‐Rule Consensus Trees

Abstract: The use of majority‐rule consensus trees as a means of resolving ambiguity in phylogenetic analyses is investigated. It is shown to be an inappropriate method for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Bootstrapping and majority rule consensus may be a strategy for improving the structure of morphometric trees when within-taxon variation is large compared to between-taxon variation. Because of this, the issues with majority-rule and morphometric data are different from those associated with majority-rule and discrete-character cladistic trees, which were criticized by Sharkey and Leathers (2001).…”
Section: Phylogenetic Components Of Shape Variancementioning
confidence: 99%
“…Bootstrapping and majority rule consensus may be a strategy for improving the structure of morphometric trees when within-taxon variation is large compared to between-taxon variation. Because of this, the issues with majority-rule and morphometric data are different from those associated with majority-rule and discrete-character cladistic trees, which were criticized by Sharkey and Leathers (2001).…”
Section: Phylogenetic Components Of Shape Variancementioning
confidence: 99%
“…The MRC is a form of consensus that pre- serves all clades present in the majority (i.e., in more than 50%) of the obtained set of equally parsimonious cladograms (Margush and McMorris 1981). The 50% rule ensures that all included clades are compatible (Sharkey and Leathers 2001). In spite of some criticism (e.g., Sharkey and Leathers 2001), several authors are using MRC as a method of weighting clades to solve ambiguous strict consensus trees (e.g., Swofford 1991, Candall and Fritzpatrick 1996, Titus and Larson 1996, Lutzoni 1997.…”
Section: Methodsmentioning
confidence: 99%
“…The strict consensus is often deemed too strict, or insensitive, especially when taxa with a significant amount of missing data (e.g., fossils) are considered (e.g., Wilkinson 1994Wilkinson , 2003. Concerning the majority-rule consensus, it has been demonstrated that when ambiguity is rampant within a data matrix, especially because of missing data, biases in the method may drive the consensus tree toward the most ambiguous set of topologies (Sharkey & Leathers 2001;Sumrall et al 2001). Finally, the interpretation of the Adams consensus if often ambiguous because it does not represent common components/clades as strict and majority-rule consensus do, but common nestings (see Wilkinson 1994 andKitching et al 1998 for an introduction to the literature relating to consensus trees).…”
Section: Interpretation Of Consensus Treesmentioning
confidence: 99%